Deploying applications in multi-san smp clusters - Alves, Albano Agostinho Gomes (2009)
The effective exploitation of multi-SAN SMP clusters and the use of generic clusters to support complex information systems require new approaches; multi-SAN SMP clusters introduce new levels of parallelism and traditional environments are mainly used to run scientific computations. In this paper we present a novel approach to the exploitation of clusters that allows integrating in a unique metaphor: the representation of physical resources, the modelling of applications and the mapping of application into physical resources. The proposed abstractions favoured the development of an API that allows combining and benefiting from the shared memory, message passing and global memory paradigms.